Covid-19 Pandemic: Force Majeure or Hardship based on the Principle of Good Faith in The Employment Agreement - Junaidi, Junaidi; Surahmi, Mila (Faculty of Law, Universitas Negeri Semarang, 2023)
A Covid-19 pandemic is an event that occurs beyond the parties' control and the parties' fault. However, applying force majeure and hardship in the event of a failure to fulfill achievements in the work agreement is subjective and cannot be used as a general principle. Its application must be carried out by analyzing case by case because not all entrepreneurs are affected by the Covid-19 pandemic, which then causes entrepreneurs to be unable to fulfill their obligations as debtors in work agreements. The employment relationship between workers and the company must obtain legal protection. The method used in this research is normative juridical. Normative research is where the law is conceptualized as what is written in a statutory regulation (law is books) or the law is conceptualized as a rule or norm that is used as the basis for human behavior as a benchmark for good or bad. The purpose of this study is to obtain a solution to termination of employment due to the Covid-19 pandemic by applying the principle of force majeure or hardship in the employment agreement. Research findings suggest that the principle of hardship has not been regulated in positive law in Indonesia, so business activities in Indonesia in general still depend on the force majeure principle as a clause included in agreements and dispute resolution. Companies that terminate employment relations should be replaced by postponing regular work or renegotiating contracts known as hardship